Bank profitability in the Euro area: The asymmetric effects of common supervision - Ioanna Avgeri; Yiannis Dendramis; Helen Louri (London School of Economics and Political Science (LSE), European Institute, 2021)
In the years after the financial crisis low bank profitability has been a major issue. The increased regulation imposed in the wake of the crisis has often been accused of overburdening banks and contributing to low profitability. The euro area, consisting of 19 different economies, made a big step in 2014 when it adopted a common supervisory mechanism introducing a heavy regulatory framework. The scope of this paper is to examine the effect that the establishment of the Single Supervisory Mechanism (SSM) in 2014 has had throughout the profitability distribution of 78 directly supervised euro area banks. We employ unconditional quantile regression analysis with panel data covering the period 2011-2017. Our main findings indicate a robust positive effect of the SSM in the lower quantiles of the bank profitability distribution, while the effect in the upper quantiles depends on the profitability index examined. The introduction of the SSM was also found to reduce the probability of bank insolvency, the effect being stronger for weaker banks. Such positive consequences for profitability, stability and convergence should be taken into account by policy makers as we move towards the next reforms of the European Banking Union.
Keywords: 330; European Banking Union; SSM; Single Supervisory Mechanism; Bank profitability; quantile regression